Beispiel Nr: 07
$ \text{Gegeben:} \\ \text{Ebene: } \vec{x} =\left( \begin{array}{c} a1 \\ a2 \\ a3 \\ \end{array} \right) + \lambda \left( \begin{array}{c} b1 \\ b2 \\ b3 \\ \end{array} \right) + \sigma \left( \begin{array}{c} c1 \\ c2 \\ c3 \\ \end{array} \right) \\ \text{Gesucht:} \text{Ebene in Koordinatenform: } n_1 x_1+n_2 x_2+n_3 x_3+k=0 \\ \\ \text{Determinante}\\ \textbf{Gegeben:} \\ \vec{x} =\left( \begin{array}{c} 0 \\ 5 \\ 0 \\ \end{array} \right) + \lambda \left( \begin{array}{c} 4 \\ -2 \\ -3 \\ \end{array} \right)+ \sigma \left( \begin{array}{c} -5 \\ 6 \\ 2 \\ \end{array} \right) \\ \\ \\ \textbf{Rechnung:} \\ \vec{x} =\left( \begin{array}{c} 0 \\ 5 \\ 0 \\ \end{array} \right) + \lambda \left( \begin{array}{c} 4 \\ -2 \\ -3 \\ \end{array} \right) + \sigma \left( \begin{array}{c} -5 \\ 6 \\ 2 \\ \end{array} \right) \\ D=\begin{array}{|ccc|} x_1-0\ & 4 & -5\\ x_2-5&-2 & 6\\ x_3-0& -3 & 2 \\ \end{array} \begin{array}{cc} x_1-0\ & 4 \\ x_2-5&-2 \\ x_3-0& -3 \end{array} =0 \\ (x_1-0) \cdot \left(-2\right) \cdot 2+ 4 \cdot 6 \cdot (x_3-0) + \left(-5\right) \cdot (x_2-5) \cdot \left(-3\right) \\ - \left(-5\right) \cdot \left(-2\right) \cdot (x_3-0) - (x_1-0) \cdot 6 \cdot \left(-3\right) - 4 \cdot (x_2-5) \cdot 2=0 \\ 14 x_1+7 x_2+14 x_3-35=0 \\ 14 x_1 +7 x_2 +14 x_3 -35 = 0 \\ \text{Koordinatenform in Hessesche Normalenform HNF} \\ 14 x_1+7 x_2+14 x_3-35=0 \\ \vec{n} = \left( \begin{array}{c} 14 \\ 7 \\ 14 \\ \end{array} \right) \\ \text{Länge des Normalenvektors} \\ \left|\vec{n}\right| =\sqrt{n_1^2+n_2^2+n_3^2} \\ \left|\vec{n}\right| =\sqrt{14^2+7^2+14^2} \\ \left|\vec{n}\right| =21 \\ \text{HNF:} \dfrac{14 x_1+7 x_2+14 x_3-35}{21}=0 \\ \\ $